2020
DOI: 10.20517/2574-1225.2019.74
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus open and video-assisted thoracoscopic surgery approaches for lobectomy

Abstract: More and more data are available on the benefits of minimally invasive thoracic surgery compared to open thoracic surgery in the curative treatment of early-stage non-small cell lung cancer. However, results are conflicting, especially when video-assisted thoracoscopic surgery (VATS) is compared to robotic-assisted thoracoscopic surgery (RATS) for lobectomy. Our goal is to report the main results of recent systematic reviews and meta-analyses comparing RATS, VATS, and open surgery for lobectomy. Using PubMed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…The ideal approach should minimize patient morbidity in order to enhance recovery, ensure a return to daily activities in a reasonable period of time and maximize oncologic outcomes. Minimally invasive approaches have long been established as suitable for resection of early-stage lung cancer [ 21 , 22 ], but no prospective randomized trials evaluating their relative efficacy and oncologic equivalence in comparison to open surgery are yet available. Indeed, comparative studies between VATS, RATS and open surgery are lacking, with most of them investigating short-term outcomes and providing poor evidence of comparable long-term oncological results.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal approach should minimize patient morbidity in order to enhance recovery, ensure a return to daily activities in a reasonable period of time and maximize oncologic outcomes. Minimally invasive approaches have long been established as suitable for resection of early-stage lung cancer [ 21 , 22 ], but no prospective randomized trials evaluating their relative efficacy and oncologic equivalence in comparison to open surgery are yet available. Indeed, comparative studies between VATS, RATS and open surgery are lacking, with most of them investigating short-term outcomes and providing poor evidence of comparable long-term oncological results.…”
Section: Discussionmentioning
confidence: 99%
“…At the posterior end of a thoracotomy wound (especially where a portion of rib has been excised), other adjuncts such as oxidised cellulose or active flowable haemostat (gelatin & thrombin) can be used [ 54 , 62 ]. The use of VATS and RATS in Thoracic Surgery has increased [ 63 , 64 ]. Use of electrocautery for adequate haemostasis is important particularly in robotics, where the ports are tight with the movement of the arms.…”
Section: Specificities Of Thoracic and Robotic Surgerymentioning
confidence: 99%
“…More recent randomised trials however have reported no difference in postoperative measures including major complications and 30 and 90 day mortality between patients having undergone lobectomy versus segmentectomy [23,24]. Technological developments resulted in introduction of robot-assisted thoracoscopic surgery (RATS), which provides an option for a minimally invasive thoracic surgical approach with evidence of improved short-term outcomes compared with VATS and no signifi cant difference in fi ve-year overall survival [25]. Robotic surgery allows for greater precision and manoeuvrability as evidenced by the results of a propensity matched study comparing robotic to open lobectomy, which showed an increase in median node evaluation with robotic resection [26].…”
mentioning
confidence: 99%